2004
DOI: 10.1063/1.1819510
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and charge distribution of potassium iodide intercalated single-walled carbon nanotubes

Abstract: Recently, potassium iodide was inserted into single-walled carbon nanotubes. We present here a first-principles density-functional theory calculation of the electronic and optical properties of a potassium iodide intercalated (10,10) nanotube. Band structure, density of states, and charge distribution of the intercalated nanotube are determined. Significant changes in the electronic structure of carbon nanotube are found upon the intercalation. In particular, the electron distribution on the tube becomes more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 14 publications
2
21
0
Order By: Relevance
“…Further, electron depletion in metallic nanotubes is always related to longitudinal contraction. 19 Density functional theory calculations of KI encapsulation in a larger (d t > d t optimum ), (10, 10) nanotube have shown that the electronic density of the nanotube wall can indeed decrease after filling, 34 consistent with our findings. Note that ref 34 found the chargetransfer process in this system to be quite complex, as on the other hand, the electronic density in the nanotube-filling interspace was found to increase.…”
Section: High-energy Vibrational Modessupporting
confidence: 92%
“…Further, electron depletion in metallic nanotubes is always related to longitudinal contraction. 19 Density functional theory calculations of KI encapsulation in a larger (d t > d t optimum ), (10, 10) nanotube have shown that the electronic density of the nanotube wall can indeed decrease after filling, 34 consistent with our findings. Note that ref 34 found the chargetransfer process in this system to be quite complex, as on the other hand, the electronic density in the nanotube-filling interspace was found to increase.…”
Section: High-energy Vibrational Modessupporting
confidence: 92%
“…12 A lot of nanomaterials have been fabricated by means of filling CNTs. 13 Much research work has been done to study the metallic nanowires. For example, the structures of ultrathin copper nanowires encapsulated in carbon nanotubes have been carried out by Choi et al 14 The structues and magnetic properties of iron encapsulated in the single-wall carbon nanotubes have also been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Atoms or molecules could be further intercalated into carbon nanotubes. [12][13][14][15][16] In this work, we mainly focus on electronic and optical properties of zigzag double-walled carbon nanotubes ͑DWCNTs͒. The effects due to the intertube interactions, the magnetic field, and the Zeeman splitting are investigated.…”
Section: Introductionmentioning
confidence: 99%